Accounting Quality, Liquidity Risk, and Post‐Earnings‐Announcement Drift - Chen, Jeff Zeyun; Lobo, Gerald J.; Zhang, Joseph H. (Contemporary Accounting Research, 2017)
Abstract Recent microstructure research finds that liquidity risk, in particular its information component, plays an important role in explaining the post‐earnings‐announcement drift ( PEAD ). We decompose liquidity risk into an accounting‐associated component and a nonaccounting‐associated component and examine their relative importance in explaining PEAD . Our research is motivated by recent findings that liquidity risk is a systematic risk and earnings quality is negatively associated with liquidity risk. We find that the accounting‐associated component is more strongly related to PEAD returns than is its nonaccounting‐associated counterpart. Further analyses reveal that the relation between accounting‐associated liquidity risk and PEAD returns is weaker for firms with greater analyst following. We also find that in a significant market downturn, the relation between accounting‐associated liquidity risk and PEAD returns becomes more pronounced. Our study is the first to document a liquidity risk‐based role of accounting quality in explaining the PEAD phenomenon. It parses out the PEAD risk premia associated with accounting versus nonaccounting sources and, by so doing, sheds light on the role of accounting quality in shaping the liquidity risk‐ PEAD returns relation.